On the peculiarities of electrical conductivity in ARC plasma containing stainless steel and tungsten - Porytskyy, P.V. (Вопросы атомной науки и техники, 2018)
The influence of stainless steel and tungsten impurities on the electrical conductivity of multicomponent arc plasma is considered in the ambient atmosphere of argon and air. The calculations are carried out on the base of Grad’s method, and it is shown that a small amount of metal causes the essential changes in the values of electrical conductivity in comparison with the case of pure gaseous mixtures. It is revealed that the increasing of metal concentration leads to the decreasing of electrical conductivity under the certain conditions in arc plasmas. Розглянуто вплив домішок нержавіючої сталі та вольфраму на електричну провідність багатокомпонентної електродугової плазми в атмосфері сумішей аргону та повітря. Проведені розрахунки ґрунтувалися на методі моментів Ґреда. Показано, що невелика кількість металевих домішок може суттєво змінити величину коефіцієнта електричної провідності порівняно із випадком чистого аргону або повітря. Виявлена можливість зменшення електричної провідності внаслідок збільшення концентрації вольфраму або нержавіючої сталі в плазмовій суміші. Рассмотрено влияние примесей нержавеющей стали и вольфрама на электрическую проводимость многокомпонентной электродуговой плазмы в атмосфере смесей аргона и воздуха. Проведенные расчеты основывались на методе моментов Грэда. Показано, что незначительное количество примесей металла может существенно изменить величину коэффициента электрической проводимости в сравнении со случаем чистого аргона или воздуха. Выявлена возможность уменьшения электрической проводимости вследствие увеличения концентрации вольфрама или нержавеющей стали в плазменной смеси.